Kesadaran Pengelolaan Limbah B3 Sesuai Peraturan Perundangan - Jordan Syah Gustav; Sari, Rizqy Kartika; Nurriwanti, Nabylla Sharfina Sekar (Universitas Muhammadiyah Manado, 2024)
According to legal regulations Republic of Indonesia No. 32 2009 concerning Environmental Protection and Management, it states that waste is the remaining results of activities or businesses whose reprocessing requires more effort and if the storage is not carried out properly it will pollute the environment. Hazardous and toxic waste is classified into three types based on its nature: liquid waste, solid waste, and gas waste. According regulations No. 74, 2001 concerning the Processing of Hazardous and toxic Materials, Hazardous and toxic Waste is the remainder of a business and/or activity that contains hazardous and/or toxic materials which due to their nature and/or concentration and/or quantity, either directly or indirectly, can pollute and/or damage the environment, and can endanger the environment. The implementation of Community Service activity focus on increase Awareness of Hazardous and toxic Waste Management in accordance with laws and regulations, To store and manage Hazardous and toxic Waste in the workplace. The implementation of this Community Service activity was carried out online in August 2024 inviting workers and prospective fresh graduates who were interested in fulfilling aspects of Hazardous and toxic waste management. The results of this activity the pre-test and post-test showed that webinar participants, increase in knowledge about Hazardous and toxic waste of 72%. A significant increase in knowledge is expected to improve community behavior regarding Hazardous and toxic waste.